2012
DOI: 10.1016/j.conbuildmat.2012.02.062
|View full text |Cite
|
Sign up to set email alerts
|

Properties and durability of HPC with tyre rubber wastes

Abstract: An estimated 1000 million tyres reach the end of their useful lives every year and 5000 millions more are expected to be discarded in a regular basis by the year 2030. Up to now a small part is recycled and millions of tyres are just stockpiled, landfilled or buried. This paper presents results about the properties and the durability of HPC with partial replacement of sand by tyre rubber wastes. Fly ash and metakaolin are used as partial cement replacement. The durability performance was assessed by means of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
73
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(79 citation statements)
references
References 15 publications
2
73
0
4
Order By: Relevance
“…The lowering influence of capillary permeability may be explained by the fact that the C-S-H gel formation in the presence of fly ash reduces the capillary water absorption of the samples by reducing the porosity. Azevedo et al (2012) studied similar concrete compositions (but without nano-TiO 2 ) with same w/b, reported that the mixture with 30% fly ash has demonstrated much higher capillary than the control mixture. The only differences between his study and current study concern the cement which was type II (clinker content between 65 and 79%) in previous investigations and type I (clinker content between 95 and 100%) in the current study.…”
Section: Resultsmentioning
confidence: 99%
“…The lowering influence of capillary permeability may be explained by the fact that the C-S-H gel formation in the presence of fly ash reduces the capillary water absorption of the samples by reducing the porosity. Azevedo et al (2012) studied similar concrete compositions (but without nano-TiO 2 ) with same w/b, reported that the mixture with 30% fly ash has demonstrated much higher capillary than the control mixture. The only differences between his study and current study concern the cement which was type II (clinker content between 65 and 79%) in previous investigations and type I (clinker content between 95 and 100%) in the current study.…”
Section: Resultsmentioning
confidence: 99%
“…One of the possible solutions for the use of waste tire rubber is to incorporate into cement concrete, to replace some of the natural aggregates. This attempt could be environmental friendly (as it helps to dispose the waste tires and prevent environmental pollution) and economically viable as some of the costly natural aggregates can be saved (Khalid and Mathew, 2012;Azevedo et al, 2012). Eldin and Senouci (1993) were the first to study on aggregates derived from used tires.…”
Section: Introductionmentioning
confidence: 98%
“…By the year 2030, the number would reach to 1200 million yearly. Including the stockpiled tires, there would be 5000 million tires to be discarded on a regular basis (Azevedo et al, 2012). If the Indian scenario is considered, it is estimated that the total number of discarded tires would be 112 million per year after retreading twice (Mukul, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…TRR is usually disposed on landfills, however, due to its difficult decomposition and considerable reduction of the useful life of landfills with this practice, disposal has proved to be environmentally impracticable [6]. By 2030, roughly 5 billion tires will be discarded yearly without sustainable destination [19]. Several alternatives have already been studied in the construction industry to manage TRR, among which the production of asphalts, sports floors, road barriers, acoustic insulation panels and expansion joints [20].…”
Section: Introductionmentioning
confidence: 99%